Therodynamic Studies on Complexation of Cu2+, Ag+ and Tl+ Metal Cations with 4?, 4?,(5?)-ditert-butyldibenzyl-18-crown-6 in Acetonitrile- Dimethylformamide Binary Solutions - Mohajeri, Massoumeh; Hossein Rounaghi, Gholam; Sedagat, Saman (Asian Journal of Chemistry, 2010)
log Kf, ΔHº and ΔSº values are reported for the complexation reactions of Cu2+, Ag+ and Tl+ metal cations with macrocyclic ligand, 4′,4″,(5″)-ditert-butyldibenzyl-18-crown-6 (DTDB18C6) in acetonitrile-dimethylformamide binary solutions (AN-DMF) at different temperatures, using conductometric method. The conductance data show that in most cases, the stoichiometry of the complexes formed between DTDB18C6 and these metal cations is 1:1 (M:L). The values of log Kf of the complexes are sensitive to the solvent composition and it was found that the stability sequences of the complexes are changed with the composition of acetonitriledimethylformamide binary solution, and in some cases, the stability order is changed with the composition of the binary solution. The values of the thermodynamic quantities (ΔHcº, ΔScº) for formation of (DTDB18C6-Cu2+), (DTDB18C6-Ag+) and (DTDB18C6-Tl+) complexes were obtained from the temperature dependence of the stability constants and the results show that in most solution systems, the complexes are enthalpy stabilized but entropy destabilized.